Assessing the Physicochemical Stability of a Compounded Neonatal Trace Element Solution - Sanaee, Forugh; Mysak, Tania; Sanderson, Laurine; Donaldson, Theresa; Vakili, Mohammad Reza; Lavasanifar, Afsaneh (Journal of Pharmacy & Pharmaceutical Sciences, 2018)
PURPOSE: Alberta Health Services (AHS) recommends the adoption of a new neonatal multi-trace element formulation containing zinc sulfate, copper sulfate, selenious acid and sodium iodide to be compounded internally in appropriate AHS pharmacies. The objective of this study was to assess the physicochemical stability of this formulation under commonly used storage conditions. METHOD: Three batches of trace element solution were compounded by University of Alberta Hospital pharmacy staff using sterile compounding procedures. Appropriate amount of zinc sulfate (500 mg/mL), copper sulfate (40 mg/mL), selenious acid (4 mg/mL), sodium iodide (2 mg/mL) and sterile water for injection were mixed. Samples from each batch were divided in individual vials and syringes for each time point and kept protected from light either at room temperature (15–30°C) or fridge (2-8°C). Vial samples were also kept at room temperature for 12 h and then transferred to fridge. Vial samples were analyzed at time 0, 12 h, and 1, 3, 7, 9, 30, 60, 90 days for their physical appearance and pH, then centrifuged and assessed for the soluble zinc (atomic absorption), copper (atomic absorption), selenium (ICP-MS) and iodine (HPLC and ICP-MS) concentrations. Syringe samples were tested at time 0 and 12 h for element concentrations. RESULTS: Under all storage conditions, when stored in vials, samples’ appearance, pH and soluble zinc, copper and selenium concentrations stayed within the USP acceptable limits up to 90 days. Iodine concentration was within the permitted limits only up to 7 days. The USP recommended HPLC method of iodine analysis seemed inadequate for this preparation and needed modifications, through frequent washing of the column with KI (2 %) solution. Samples kept in syringes at room temperature, showed lower than permitted concentration of Zn at 12h in this study. CONCLUSION: The AHS neonatal multi-trace element formulation seem to be physio-chemically stable up to 7 days in all three storage conditions when kept in vials. A decline in iodine concentration is seen after 7 days irrespective of storage conditions. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.